ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL AKM TIPE URAIAN BERDASARKAN TEORI NEWMAN - Rina Agustina; Tri Nova Ayu Permadani; Tri Widiyarsih; Yulia Cahya Praswati (Universitas Muhammadiyah Metro, 2022)
This study aims to analyze students' errors in completing the explanation of the SPLDV material with Newman's theory. The method of this research is descriptive qualitative. The subject of this research was class X students in the even semester of the 2020/2021 academic year with consists of 10 students. Data collection techniques used are written tests and interviews. The instrument used a SPLDV problem test. Based on the results of data analysis, that in completing the SPLDV material, he made a mistake; (1) Reading Errors with the type of error that occurs in students who cannot read the words proposed because they are in a hurry to understand the meaning given so that there is an understanding of the concept, (2) Understanding) Errors with the types of errors that often occur in students who do not continue the process after determining what is known and developed because students do not understand the next steps that need to be taken to solve the problems given, (3) Transformation Errors with frequent types of errors. occurs when students do not change information into a linear equation but can change it but it is not correct because of the lack of understanding of students in answering questions when doing mathematical models, (4) Process Skill Errors with errors that often occur Students do miscalculation due to tortoise The accuracy of the students in solving them, and (5) Encoding Errors with errors that often occur in students not being concluded correctly because students have completed calculations.